Erin McGlothlin, Brad Preger, and Markus Zisselsberger, editors. The Construction of Testimony: Claude Lanzmann’s Shoah and Its Outtakes. Wayne State UP, 2020. - Michael Williamson (Studies in 20th & 21st Century Literature, 2022)
Review of Erin McGlothlin, Brad Preger, and Markus Zisselsberger, editors. The Construction of Testimony: Claude Lanzmann’s Shoah and Its Outtakes. Wayne State UP, 2020. 495 pp.
Keywords: Holocaust; film; archive